Strategi Komunikasi Politik Cicha Koeswoyo Sebagai Calon Anggota Legislatif DPRD PDI-Perjuangan Dapil 7 Jakarta Pusat - Barizki, Rezzi Nanda (CAKRAWALA: JURNAL HUMANIORA BINA SARANA INFORMATIKA, 2024)
Political competition in Jakarta’s South Electoral District 7 requires an effective communication strategy, especially for legislative candidates navigating complex demographics and tight electoral dynamics. Cicha Koeswoyo, a candidate from PDI-Perjuangan, capitalized on her celebrity background, local connection, and issue focus on women, children, health, and education to secure electoral success. This study aims to analyze Cicha Koeswoyo’s political communication strategies in her campaign for the Jakarta Provincial DPRD (2024–2029). A descriptive qualitative approach was employed, examining personal narratives, campaign slogans, policy pillars, the use of traditional and digital media, and the role of party machinery. The analysis highlights the interplay of personal branding, authenticity, and issue-based communication. Cicha Koeswoyo’s strategy is characterized by issue consistency, demonstrations of tangible actions, and leveraging celebrity status as initial capital. Concrete actions, such as providing Posbindu health equipment and conducting fogging, strengthened her narrative of “action over rhetoric.” The synergy with PDI-Perjuangan’s machinery complemented her individualized campaign initiatives. She secured 15,578 votes, underscoring the effectiveness of her approach in a highly competitive electoral landscape. Cicha Koeswoyo’s success demonstrates that a blend of personal image, issue-based advocacy, and visible actions is essential for effective political communication. To sustain political legitimacy, her communication strategy must evolve toward participatory, transparent, and continuous governance.